Detection Financial Statement Fraud With Beneish Model : An Empirical In Indonesia - Mutia Kusumasanthi, Kartika Hendra Titisari & Anita Wijayanti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to know the number of manufacturing companies that classifiedas manipulators, gray company, and non-manipulators which measure usedBeneish analysis model. Used samples consisted of 64 annual financial reports ofmanufacturing companies that listed in Indonesia Stock Exchange from 2015 to2016. The results of data analysis show there are 5 firms with percentage 7,81%classified as manipulators. Most dominant indicators are SGAI, DEPI, and AQI.Number of gray company category are 2 or 3,81% .Most commonly shown byGMI indicator. While the companies that classified as non-manipulators are 57companies or 89,06%. The results of this research indicate that (1) still founds acompanies that have potential to do financial statement fraud, even the numberincreased, as much as 5 companies or equal to 7,81% from samples companies. (2)as many as 2 companies or 3,13% of total samples companies classified as graycompany. (3) there are 57 companies or 89,1% classified as non-manipulators.Investors and creditors are expected to be more cautious in deciding the company'scapital and credit policies in the future. While for companies that have presentedfinancial statements that are free from the element of manipulation should berewarded. In the long run, companies can enjoy good market performance and inturn gain public trust.Keywords : financial statement fraud; manipulator; gray company; non-manipulators; Beneishanalysis.